Influence of TiOSO₄ on the kinetics of formation and protective properties of oxide coatings on AISI 304 steel - Shtefan, Viktoriia; Kanunnikova, Nadiia (Національний технічний університет "Харківський політехнічний інститут", 2025)
The influence of titanium thiosulfate, introduced into an aqueous electrolyte, on the features of electrochemical formation of oxide coatings on AISI 304 stainless steel has been studied, with a focus on changes in anodic process kinetics, electrochemical passivation parameters, and the protective properties of the resulting layer. The changes in the transition potential to the passive state, the width of the passive region, and the passivation current density depending on the titanium concentration in the electrolyte were analyzed. It was shown that increasing the content of titanium thiosulfate in the solution promotes a decrease in the passivation onset potential and the formation of a denser protective layer, as evidenced by an increase in polarization resistance and a decrease in anodic current density. Emphasis was placed on the optimal concentration range of TiOSO₄ (20 g/L), which ensures maximum efficiency in the formation of the passive layer. Results of potentiodynamic polarization studies in a 3% sodium chloride solution were analyzed, indicating a significant influence of the titanium-containing component on the electrochemical behavior of the steel. It was shown that samples with oxide coatings formed in modified electrolytes are characterized by a shift of the corrosion potential toward more electropositive values by 500–800 mV compared to untreated steel. It was confirmed that the obtained coatings effectively reduce the electrochemical activity of the metal in a chloride environment, as evidenced by a significant reduction in corrosion current density and an increase in polarization resistance. Розглянуто вплив тіосульфату титану, введеного до складу водного електроліту, на особливості електрохімічного формування оксидних покриттів на нержавіючій сталі марки AISI 304, з акцентом на зміну кінетики анодних процесів, електрохімічних параметрів пасивації та захисних властивостей сформованого шару. Проаналізовано зміну потенціалу переходу в пасивний стан, ширини пасивної області та густини струму пасивації залежно від концентрації титану в електроліті. Показано, що підвищення вмісту тіосульфату титану у розчині сприяє зниженню потенціалу початку пасивації та формуванню щільнішого захисного шару, що проявляється у зростанні поляризаційного опору та зниженні густини анодного струму. Акцентовано увагу на оптимальному діапазоні концентрацій TiOSO₄ (20 г/л), за якого забезпечується максимальна ефективність формування пасивного шару. Проаналізовано результати потенціодинамічних поляризаційних досліджень у 3%-му розчині натрій хлориду, що вказують на суттєвий вплив титановмісного компонента на електрохімічну поведінку сталі. Показано, що зразки з оксидними покриттями, сформованими у модифікованих електролітах, характеризуються зсувом корозійного потенціалу в область більш електропозитивних значень на 500–800 мВ порівняно з необробленою сталлю. Підтверджено, що одержані покриття ефективно знижують електрохімічну активність металу в хлоридному середовищі, що проявляється в істотному зменшенні густини корозійного струму та збільшенні поляризаційного опору.
В TiOSO₄ на кінетику формування та захисні властивості оксидних покриттів на сталі AISI 304
Keywords: anodizing of steel; titanium thiosulfate; polarization behavior; passivation; chronopotentiometry; corrosion resistance; oxide coating; анодування сталі; тіосульфат титану; поляризаційна поведінка; пасивація; хронопотенціометрія; корозійна стійкість; оксидне покриття